Ein Schreiblehrkonzept für interdisziplinäre Module in den Ingenieurwissenschaften - Rzehak, Kristina; Kaimann, Andrea (Schreiblehrkonzepte an Hochschulen. Fallstudien und Reflexionen zum Schreibenlehren und -lernen)
This paper presents a teaching concept of academic writing for the interdisciplinary course gender and diversity at the faculty of engineering and mathematics (University of Applied Sciences Bielefeld). The concept is based on three main principles: disciplinary specialization, needs orientation and progressive acquisition of competencies. These principles are seen as transferable to other courses. The students of the course are supported by lectures, materials and formative feedback that is tailor-made for their needs and their interdisciplinary writing task. Already during the course, the students produce certain text parts of their writing tasks such as a bibliography, an exposé and a structure. Within 1 or 2 weeks, they will receive individual written feedback on each of these text parts. Despite methodical reservations, the paper presents some considerations with regard to the effectiveness of the concept. Firstly, a self-assessment survey shows that the students feel they have acquired competencies in writing and literature research after the completion of the course. Secondly, the grading was analysed by comparison to a control group of students who were not part of the teaching concept. Whereas the grade point average does not differ, the percentage of texts that do not meet the minimum requirements dropped within the group of students who completed the course.